Reviews. (1st September 2014) - Hill, Katie; Gladston, Paul; Carrier, David
Book from the Ground. From Point to Point, Xu Bing (2014) Cambridge, MA: The MIT Press, 128 pp., ISBN: 9780262027083, h/bk, £17.95The Book About Xu Bing's Book from the Ground, Mathieu Borysevicz (ed.) (2014) Cambridge, MA: The MIT Press, 160 pp., ISBN: 9780262027427, h/bk, £17.95Modern Poetry in China: A Visual-Verbal Dynamic, Paul Manfredi (2014) Amherst, NY: Cambria Press, 244 pp. ISBN: 9781604978629, h/bk £35.00Ink Art: Past as Present in Contemporary China Metropolitan Museum of Art, New York, 11 December 2013–6 April 2014